Splenic artery embolization with detachable balloons for hypersplenism. Issue 10 (October 2018) - Pang, Xiaoxi; Li, Tengyu; Wang, Cheng'en
Objective: This study was performed to investigate the efficacy of proximal splenic artery embolization using detachable balloons for patients with hypersplenism and portal hypertension. Methods: Twelve patients diagnosed with hypersplenism with thrombocytopenia or leukocytopenia caused by portal hypertension were treated by proximal splenic artery embolization with detachable balloons and metallic fibered coils. All patients were followed for up to 6 months. Blood parameters, coagulation factors, and liver function indicators were measured. Enhanced computed tomography and abdominal ultrasonography examinations were also performed in advance to confirm the infarction area and evaluate the changes in spleen size. Results: Postoperative angiography demonstrated complete embolization of the proximal splenic artery in all 12 patients. Thrombocyte and leukocyte counts rose significantly in all patients in 2 weeks and stayed significantly higher than those before embolization throughout the 6-month follow-up. The total bilirubin concentration and prothrombin activity recovered significantly and returned to normal levels 6 months later. Computed tomography revealed partial infarction and liquefaction of the splenic parenchyma in nine patients. Conclusions: Proximal splenic artery embolization using detachable balloons could be considered a safe and effective therapeutic modality in alleviating hypersplenism secondary to portal hypertension.